The Influence of Sleep Quality on The Health of Migrant Students in The City of Bandung - Azahra, Astrid Sulistya; Prabowo, Agung; Saputra, Jumadil (Corespub, 2024)
of Bandung, as a group that faces unique challenges related to adapting to new environments and lifestyles, often experience problems related to the quality of their sleep. Urban environmental factors such as noise, bright light, and air pollution can affect their sleep patterns. This study uses a longitudinal observational approach to investigate the influence of sleep quality on the health and academic achievement of migrant students. Data were collected via questionnaires and, where possible, sleep measuring devices. The analysis results show a significant correlation between sleep quality, physical health, mental health, and academic achievement. College students with better sleep patterns tend to have better physical health, lower stress levels, and higher academic achievement. The implication of this research is the importance of supporting the sleep quality of overseas students through educational programs and accessibility to mental health resources. Lifestyle factors such as a balanced diet, adequate physical activity, and stress management are also important in improving sleep quality. This research provides in-depth insight into the factors that influence the sleep quality of migrant students and provides a basis for the development of interventions that support their well-being and academic success in urban environments.